The Effect of Interest Income and Interest Expense on Net Income at State-Owned Banks Listed on the IDX 2021 - Aulia Aulia; Ayu Kurnia Sari; Dian Anggraini (Ridwan Institute, 2022)
This study aims to determine the effect of interest income and interest expense on net income for the period 2012 to 2020. The research method used is a quantitative method using data sources from the financial statements of Concise Profit and Loss for the period 2012 to 2020. The data analysis technique uses data normality test, Pearson Product correlation analysis. Moment, coefficient of determination, and multiple linear regression analysis. Based on the results of data analysis, knowing the effect of Interest Income and Interest Expense on Net Profit states that the data is normally distributed, the closeness of the relationship is 0.494 strong category, the direction of the influence is positive. Interest Income and Interest Expense affect Net Profit by 85.4% and the remaining 14.4% is influenced by other variables. it is known that t count (6.088) > t table (2.034) and significant 0.000 <0.05. This means that partially interest income has a positive effect on net income at state-owned banks listed on the Indonesia Stock Exchange, then t count (-2.382) > t table (2.034) and significant 0.023 <0.05. This means that partially interest expense has a negative effect on net income at state-owned banks listed on the Indonesia Stock Exchange. Furthermore, it is known that F count is 103.149 > F table 3.28, with a significance of 0.000 <0.05. This shows that all independent variables, namely interest income and interest expense, simultaneously have a significant effect on net income at state-owned banks listed on the Indonesia Stock Exchange.